Model mentoring pembinaan akhlak santriwati di Perguruan Islam Ar-Risalah - Satria, Rengga Satria; Husna, Salsabila Fitri (Ta'dibuna: Jurnal Pendidikan Islam, 2022)
Ar-Risalah Islamic College is an Islamic school with a dormitory system that focuses on fostering the morals of female students. The purpose of the study was to describe the mentoring model at the Ar-Risalah Islamic College in fostering the morals of students. This study uses a qualitative method. Data collection techniques are interviews, observation, and documentation. The interactive method of Miles and Huberman was used in data analysis in this study. Research shows that 1) Mentoring is the main means of moral development that has forms of activities such as recitations of the Qur'an, reading prayers, cults, rihlah, qodhoya, to cooking together. 2) moral development through mentoring in Ar-Risalah is carried out in three stages, namely worship development, character building, and environmental cleanliness. 3) supporting factors and inhibiting factors in the process of moral development a) supporting factors in the form of the closeness of mentors to students, where mentoring activities are easily accessible, is a mandatory program at Ar-Risalah Islamic College b) inhibiting factors in the form of time, number of students who attend, busyness mentors and the lack of self-awareness of the students. Abstrak Perguruan Islam Ar-Risalah adalah sekolah Islam dengan sistem asrama yang fokus kepada pembinaan akhlak santriwati. Tujuan penelitian adalah mendeskripsikan model mentoring di Perguruan Islam Ar-Risalah dalam membina akhlak santriwati. Penelitian ini menggunakan metode kualitatif. Teknik Pengumpulan data adalah wawancara, observasi dan dokumentasi. Metode interaktif dari Miles dan Huberman digunakan dalam analisis data pada penelitian ini. Penelitian menunjukkan bahwa 1) Mentoring merupakan sarana utama dalam pembinaan akhlak yang memiliki bentuk-bentuk kegiatan seperti tilawah Al Qur'an, pembacaan doa, kultum, rihlah, qodhoya, sampai memasak bersama. 2) pembinaan akhlak melalui mentoring di Ar-Risalah dilakukan melalui tiga tahap yaitu pembinaan ibadah, pembinaan karakter dan kebersihan lingkungan. 3) faktor pendukung dan faktor penghambat dalam proses pembinaan akhlak a) faktor pendukung berupa Kedekatan pembimbing dengan santriwati, tempat kegiatan mentoring mudah di jangkau, merupakan program wajib di Perguruan Islam Ar-Risalah b) faktor penghambat berupa waktu, jumlah santriwati yang hadir, kesibukan para pembimbing dan kurangnya kesadaran diri dari santriwati.